2012
DOI: 10.1111/j.1467-9590.2012.00560.x
|View full text |Cite
|
Sign up to set email alerts
|

The Reduced Ostrovsky Equation: Integrability and Breaking

Abstract: The reduced Ostrovsky equation is a modification of the Korteweg-de Vries equation, in which the usual linear dispersive term with a third-order derivative is replaced by a linear nonlocal integral term, which represents the effect of background rotation. This equation is integrable provided a certain curvature constraint is satisfied. We demonstrate, through theoretical analysis and numerical simulations, that when this curvature constraint is not satisfied at the initial time, then wave breaking inevitably o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
63
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(66 citation statements)
references
References 26 publications
3
63
0
Order By: Relevance
“…It has been shown in Ref. 38 that if the initial condition u(x, 0) ¼ u 0 (x) is such that d 2 u 0 (x)/dx 2 > c/ 3a at some x, then wave breaking eventually occurs and the solution becomes singular. If d 2 u 0 (x)/dx 2 < c/3a for all x, the solution remains smooth at all times.…”
Section: B Reduced Rkdvmentioning
confidence: 99%
“…It has been shown in Ref. 38 that if the initial condition u(x, 0) ¼ u 0 (x) is such that d 2 u 0 (x)/dx 2 > c/ 3a at some x, then wave breaking eventually occurs and the solution becomes singular. If d 2 u 0 (x)/dx 2 < c/3a for all x, the solution remains smooth at all times.…”
Section: B Reduced Rkdvmentioning
confidence: 99%
“…Once the wave front steepens sufficiently it disperses into a primary wave packet and a tail of smaller dispersive waves. We demonstrated that the nonlinear wave packet interpretation of the wave train of Grimshaw et al (2012) is appropriate in some parameter regimes, with changes in amplitude reflected in the phase of the nearly solitary wave response. By mapping out the parameter space we have shown that, as expected, the Rossby number is the controlling variable for the dynamics in this problem.…”
Section: Discussionmentioning
confidence: 99%
“…The KdV equation is the simplest model equation that allows for a balance between nonlinear and dispersive effects, with a rich mathematical structure which makes predictions of the evolution of an initial state that are remarkably robust in both laboratory and field settings (see Johnson, 1997). A rotation-modified version of the KdV equation was first derived by Ostrovsky (see Grimshaw et al, 2012 for an in-depth discussion of the equation properties and references to the Russian literature). This new equation was subsequently analysed both through theoretical solutions found by asymptotic expansions and through numerical solutions.…”
Section: Introductionmentioning
confidence: 99%
“…This construction goes back to at least the late 70's and it was revisited in several publications, [19,5,23,1,6]. In fact, the authors in [6] placed special emphasis of these explicit solutions and asked about further properties of these simple solutions.…”
Section: Spectral Stability For the Periodic Waves In The Quadratic Casementioning
confidence: 99%
“…Clearly, (6), being a fully nonlinear equation, is not a very nice object to deal with. Thus, we perform a (solution dependent) change of variables, namely…”
Section: Introductionmentioning
confidence: 99%